Potensi Geoarkeologi Wilayah Trenggalek dan Peluangnya bagi Pengembangan Geopark - J. Susetyo Edy Yuwono; Janati Prariyadiyani; Raka Pranadipta (Badan Riset dan Inovasi Nasional (BRIN), 2022)
Trenggalek Regency is one of the regencies in the southern part of East Java Province, which its landscape strongly expresses the historical influence of ancient volcanism and tectonics. Unlike the three neighboring districts, namely Ponorogo, Pacitan, and Tulungagung, the archaeological potential related to the condition of the Trenggalek region's landscape has not been studied much. Hills and mountains with steep slopes form nearly 80% of the Trenggalek area. In the south, karst hills and coastal areas are stretch from west to east, connecting with the East Pacitan karst area on the west and the Tulungagung karst area on the east. The lowlands are only found in the central part, forming an intermontane basin with the Ngasinan River as the main river. A geoarchaeological approach is needed to explore the archaeological potential by studying the uniqueness of its landscape (history and geological formations). Through this approach, this research leads to the pilot development of a geopark based on the features and uniqueness of the Trenggalek region's natural history and its correlation with the accompanying non-geological aspects, namely the diversity of archaeological and biological sites. Initial efforts were made by finding, recording, and assessing the features and uniqueness of locations that could potentially be used as geosites. This concept combines earth, cultural and biological aspects to conserve geological heritage, enhance the local economy, and education. The analysis of each element is based on a geoarchaeological perspective through spatial data processing based on the Geographic Information System (GIS). The final result is in the form of scientific knowledge about the geoarchaeological potential of the Trenggalek area and recommendations for geopark development according to the potential level of each geosite.